2016
DOI: 10.1158/2159-8290.cd-15-0894
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CDK4 and CDK6: From Discovery to Therapy

Abstract: Biochemical and genetic characterization of D-type cyclins, their cyclin D-dependent kinases (CDK4 and CDK6), and the polypeptide CDK4/6 inhibitor p16INK4 over two decades ago revealed how mammalian cells regulate entry into the DNA synthetic (S) phase of the cell division cycle in a retinoblastoma protein (RB)-dependent manner. These investigations provided proof-of-principle that CDK4/6 inhibitors, particularly when combined with co-inhibition of allied mitogen-dependent signal transduction pathways, might p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
714
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 766 publications
(759 citation statements)
references
References 137 publications
20
714
1
2
Order By: Relevance
“…Beyond the requirement for RB expression, additional factors that are considered as potential determinants of extent and duration of tumor response to palbociclib include the expression levels of p16, CDK4, and CDK6 in RB-proficient tumors as well as the expression of additional cell-cycle regulators including cyclin E and p27KIP1, and D-type cyclins. 27 These factors-and others yet to be determined-may contribute to Control vs treatment C vs PB P ¼ .012* P ¼ .004 P ¼ .001 P ¼ .001 C vs RT P ¼ .012* P ¼ .049* P ¼ .005 P < .001 C vs PB -. RT P ¼ .001 P < .001 P < .001 P < .001 C vs PB + RT P < .001 P < .001 P ¼ .001 P < .001 C vs RT -.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the requirement for RB expression, additional factors that are considered as potential determinants of extent and duration of tumor response to palbociclib include the expression levels of p16, CDK4, and CDK6 in RB-proficient tumors as well as the expression of additional cell-cycle regulators including cyclin E and p27KIP1, and D-type cyclins. 27 These factors-and others yet to be determined-may contribute to Control vs treatment C vs PB P ¼ .012* P ¼ .004 P ¼ .001 P ¼ .001 C vs RT P ¼ .012* P ¼ .049* P ¼ .005 P < .001 C vs PB -. RT P ¼ .001 P < .001 P < .001 P < .001 C vs PB + RT P < .001 P < .001 P ¼ .001 P < .001 C vs RT -.…”
Section: Discussionmentioning
confidence: 99%
“…The development of effective inhibitors for Cdk4/6 kinases has been one of the most impactful applications of pRB research (Fry et al 2004; for review, see Sherr et al 2016). Complexes of Cdk4/6 and D-type Cyclins have multiple substrates, but it is clear that pRB is one of their most important targets.…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…In a large subset of tumors retaining RB expression, alterations in cyclin-CDK pathways serve to inactivate tumor suppressor function. This is achieved either via upregulation of RB-inhibiting cyclin-CDK complex components (e.g., cyclin D1, CDK4, and cyclin E) (11)(12)(13)(14)(15)(16) or through loss of CDK inhibitors such as p16 INK4A and p27 Kip1 , both of which serve as tumor suppressors in their own right through this function (11,(15)(16)(17)(18)(19)(20)(21)(22)(23). Underscoring the importance of RB inactivation in promoting cancer cell phenotypes, CDKs have been identified as therapeutic targets, and clinical trials for CDK inhibitors have shown promise across cancer types (NCT01291017, non-small cell lung carcinoma; NCT00141297, lymphoma; NCT01958021, MONALEESA-2, breast cancer) (11,(24)(25)(26), with palbociclib (CDK4/6 inhibitor)…”
Section: Introductionmentioning
confidence: 99%
“…While tumor-specific proclivities for favoring RB retention and inactivation via CDKs versus RB loss have long been appreciated (15,16,(28)(29)(30), the underlying basis for selectivity is unknown, and the relative impact on downstream E2F1 signaling and function remains undefined. RB loss is typically achieved through genetic alterations including either genomic deletion and loss of heterozygosity or somatic mutations that generate an unstable protein (8,15,29,30).…”
Section: Introductionmentioning
confidence: 99%